Analisa Vertical Lift Performance Pada Sumur “Af” Pada Lapangan “MP” Dengan Memperhitungkan Kehilangan Tekanan Pada Tubing Untuk Mendapatkan Laju Alir Optimal - Marsel Patempe; Mirza; Rohima Sera; Engilene Marlin; Joko Wiyono; Dody Finansa (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2021)
As is known, if an oil well is produced for a long time, the pressure will decrease so that it can reduce the production rate of the well. So it is necessary to do a vertical lift performance to determine the pressure loss in the tubing during production. Where in production it is important to determine the vertical lift performance in analyzing the pressure loss in the vertical pipe. Where the purpose of this study is to calculate the pressure loss in the tubing and also to obtain the optimal flow rate in the